Global or local brand? Hotel selection in global travel context. Issue 1 (20th July 2020) - Oh, Haemoon; Lee, Misoon; Lee, Seonjeong Ally
Abstract : Purpose: This study aims to investigate how and why traveling consumers choose globally branded/operated, instead of locally branded, hotels when traveling to another country. Design/methodology/approach: Building on signaling theory, the authors conceptualize a model to explain the consumer process of selecting global hotel brands and test the model empirically with South Korean international consumers through a self-administered survey. Findings: The data support the relationships of selected brand signals, such as brand credibility, brand liability, decision heuristic and anticipated satisfaction, with brand attitude and purchase likelihood. Practical implications: The results imply how global hotel brand managers could enhance the effect of global hotel branding on the consumer's hotel choice. Originality/value: The study adds to the literature by proposing a new, empirically supported model of global branding for the tourism and hospitality industry.